The Effect Of Hedonism Lifestyle On Student Consumptive Behavior - Munajah Nasution, Amalia; Nurbaiti, Nurbaiti; Ikhsan Harahap, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
The purpose of this study is to determine how the influence of student consumption habits on the management study program at the Faculty of Economics and Islamic Business UIN North Sumatra. This hedonistic lifestyle encourages excessive consumption, which in this case is contrary to Islamic teachings. Islam prohibits excessive consumption triggered by this hedonistic lifestyle. The hypothesis of this study is that management students at the College of Economics and Islamic Business UIN North Sumatra have a positive relationship with hedonistic and consumptive lifestyles. The participants in this study were students of the Management Study Program at the Faculty of Economics and Islamic Business, UIN North Sumatra University. A total of 91 responses were obtained using the Slovin formula. This study used IBM SPSS version 27 for data analysis. According to the results of this study, hedonic lifestyle has a significant influence on consumption in management students.